2010
DOI: 10.1111/j.1754-9485.2010.02185.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Use of 3D imaging and awareness of GEC‐ESTRO recommendations for cervix cancer brachytherapy throughout Australia and New Zealand

Abstract: There has been a marked increase in the use of 3D imaging and awareness of GEC-ESTRO recommendations. Implementation and reporting of image-based gynaecological brachytherapy is strongly dependent on local resources and infrastructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Recent surveys on IGBT for cervical cancer demonstrated that CT is the most commonly used imaging modality for dose specification in clinical practice [47]. Brachytherapy for cervical cancer in Japan is rapidly transitioning from 2D to 3D treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys on IGBT for cervical cancer demonstrated that CT is the most commonly used imaging modality for dose specification in clinical practice [47]. Brachytherapy for cervical cancer in Japan is rapidly transitioning from 2D to 3D treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…The use of 3D imaging has greatly expanded since the last survey conducted throughout Australia and New Zealand in 2009, Table 2. 17,18 The high levels of CT use are to be expected as the majority of departments (79%) perform imaging in the radiotherapy departments using their own CT scanners. Use of MRI has increased from 15% to 50% in the intervening years.…”
Section: Imagingmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous reports have demonstrated that centres in Australia are adopting image-guided protocols with an increase in the use of 3D imaging in brachytherapy planning from 27% in 2005 to 65% in 2009. 17,18 The purpose of this survey was to explore the current patterns of practice for brachytherapy in cervix cancer in Australia and New Zealand. The survey was also intended to explore clinician attitudes towards IGABT and identify barriers to the implementation of IGABT.…”
Section: Introductionmentioning
confidence: 99%
“…The use of image-based brachytherapy has increased from 27% in 2005 7 to 65% in 2009. 8 The main imaging modality has been CT with only one department using MRI in 2005 increasing to three in 2009. The number of patients with cervical cancer treated in many departments can be low with 29% of centres treating 10 or less cervical brachytherapy patients per year in 2014.…”
Section: Introductionmentioning
confidence: 99%